Ocorrência do câncer do colo do útero em mulheres indígenas da Amazônia Paraense - MOTA, Rosemary Pereira da (Universidade Federal do Pará, 2018)
The present study examined the occurrence of cancer of the cervix in Indian women of the Amazon Para, in the period 2005-2012, highlighting the interest in indigenous populations affected by diseases of modernity considering the difficulties and the importance of studying the health problems of these populations influenced by inter-ethnic contacts and processes of socio-cultural and environmental change. A quantitative research based on statistical exploratory model was carried out to give support to qualitative analysis that characterized the research. We used data from the House of Indigenous Health, Bethlehem district Icoaraci ( CASAI ) , records and reference and counter-reference guides . The incidence and changes in cervical cancer, and types of treatment received, referrals were analyzed, in addition to high grounds in fourteen indigenous women, occurring at this period, characterizing their prevalence.